Quality cost in the construction industry-preliminary findings in Malaysia - Che Ali, Mukhtar (Faculty of the Built Environment University of Malaya, 2010)
One of the key areas being emphasis in ISO 9001 Quality Management System (QMS) is performance measurement towards continual improvement. Among the primary measuring tools is quality cost approach. Quality cost has been well practice in manufacturing sector but slowly gain its importance in construction industry. In fact Project Management Body of Knowledge (PMBOK) has reckoned quality cost as one of the tool and technique in few of its management processes. In view of such circumstances that has prompted an effort to undertake a study to ascertain the level of knowledge and practice on quality cost in Malaysian construction landscape. The targeted group of respondents was the personnel in the project management team. Capitalizing Construction Industry Development Board (CIDB) National Electronic Tendering Initiatives (NETI) road shows which were held in year 2007 throughout the country, the author was able to garner 263 respondents representing the project management team. Subsequently the data gathered from the completed forms were analyzed using Statistical Package for Social Science (SPSS) software. General findings indicated that the level of knowledge and practice on quality cost among the project management team were relatively low. One of the main contributing factors was poor knowledge in the area related to quality cost. Despite of such scenario most of the respondents showed their interest in acquiring knowledge in the field of quality cost. Hence quality cost approach is at the infancy stage in Malaysian construction industry.